2021
DOI: 10.3389/fphys.2021.733139
|View full text |Cite|
|
Sign up to set email alerts
|

Reinforcement Learning to Improve Image-Guidance of Ablation Therapy for Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia and currently affects more than 650,000 people in the United Kingdom alone. Catheter ablation (CA) is the only AF treatment with a long-term curative effect as it involves destroying arrhythmogenic tissue in the atria. However, its success rate is suboptimal, approximately 50% after a 2-year follow-up, and this high AF recurrence rate warrants significant improvements. Image-guidance of CA procedures have shown clinical promise, enabling the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It would have a significant impact on the future if these devices integrated with DNN were part of diagnosing and treating AF. The DRL can also contribute to the future by consolidating the treatment; for example, the selection of ablation areas for curing AF using catheter ablation can potentially be improved by DRL [23].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…It would have a significant impact on the future if these devices integrated with DNN were part of diagnosing and treating AF. The DRL can also contribute to the future by consolidating the treatment; for example, the selection of ablation areas for curing AF using catheter ablation can potentially be improved by DRL [23].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…The agent achieved 84% success rate in terminating AF during training and 72% success rate in testing. The AF recurrence rate after attempts to re-initiate AF in the two-dimensional atrial models after catheter ablation was 11%, suggesting the potential for large improvements on the existing approaches [ 107 ].…”
Section: Reinforcement Learningmentioning
confidence: 99%
“…[ 83 ] reported that not only LA morphology but also alterations in PVs could be novel imaging markers for patients with AF recurrence after CA; therefore, they used ML to extract the radiomic features of LA and PVs, respectively, and demonstrated that they could be good predictors for AF recurrence. It is worth noting that MRI-based ML will strengthen the identification of LA fibrosis by late gadolinium-enhanced MRI, thus improving the predictive ability for AF recurrence [ 89 , 90 ]. Moreover, deep learning-based LA-curved M-mode speckle tracking also provides a novel method to predict AF recurrence following CA [ 91 ].…”
Section: Use Of ML For the Prediction Of Af Recurrence After Camentioning
confidence: 99%